Pengaruh Perbandingan Tepung Kernel Biji Mangga Arum Manis (Mangifera indica L.) dan Tapioka (Manihot utilissima) Terhadap Karakteristik Biskuit Bebas Gluten - Pradnya Putri, Ni Made Meilinda; Sri Wiadnyani, Anak Agung Istri; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPADO - 10.24843/itepa.2025.v14.i01.p06, 2025)
Mango seed kernel are high in carbohydrates this can be used to make biscuits. To reduced hardness, required the addition such as tapioca. The aim of this study was to determine the effect ratio of mango seed kernel flour and tapioca on biscuits characteristics and determine the right comparison to make biscuit with the best characteristics. This research used Completely Randomized Design (CRD) with 6 treatment levels, with ratio of mango seed kernel flour and tapioca:  100:0, 90:10, 80:20, 70:30, 60:40, and 50:50, each treatment was repeated 3 times. Data was analyzed used ANOVA then by Duncan's Multiple Range Test. The observed variables are sensory, physical and chemical characteristics. The ratio of mango seed kernel flour and tapioca had a significant effect (P<0.05) on moisture content, ash, crude fiber, fat, protein, carbohydrate, hardness and texture, taste, color, aroma, and overall acceptance. The best biscuit characteristics were obtained in ratio of 50 percent mango seed kernel flour and 50 percent tapioca with 4.37 percent moisture, 1.40 percent ash, 6.09 percent protein, 31.20 percent fat, 1.44 percent crude fiber, 56.91 percent carbohydrate, hardness of 22.58 N, the texture was liked, the taste was slightly liked, the color was liked, the aroma was liked, and overall acceptance was slightly liked. Keywords : gluten free biscuit, tapioca, arummanis mango seed kernel flour